Motivation and Confidence of Pre-Service Teachers to Use English as Medium of Instruction during Teaching Practicum - Indrawati, Indrawati (PASCASARJANA IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2019)
Motivation and confidence in language teaching have always become interesting things to be observed. This study was intended to give a complementary views related to what factors might contribute to the ups and downs of how Pre-Service Teachers of English struggling to finish their teaching practicum at schools. Some supervising teachers at schools were requested to recall their memories and reopen documents about PSTs who ever conducted their teaching practice there. Their comments on how PSTs performed their instructions in the classroom might give solution to less-motivated and low confident PSTs. As a result, some courses at Tarbiyah Faculty which were given before PSTs having their teaching practicum need to be evaluated and revised.